Optimization of Halal Product Process Companions in Accelerating Halal Certification in Indonesian MSME Products - Fatchurrohman, M; Nuha, Muhammad Ulin (Indonesia Journal of Halal, 2022)
Indonesia's economic growth has entered a positive path as can be seen from the improvement on the demand side and growth from the supply side. Various improvements in leading indicators at the beginning of 2022 indicate a good economic outlook for Indonesia in the future. The continued increase in the Consumer Confidence Index (CCI) also indicates an increasing recovery in public confidence in carrying out economic activities. Meanwhile, the global economy in 2022 is projected to continue the recovery trend and will rely on the transition of the pandemic to endemic. The International Monetary Fund (IMF) projects global economic growth of 4.4%. The Indonesian government itself targets Indonesia's economic growth in 2022 at 5.2% (yoy)).      The development of product processing technology today makes it difficult for us to distinguish which ones are halal and haram, so it is necessary to ensure that the materials used are clearly traceability and guarantee halalness. Halal Product Process (HPP) is a series of activities to ensure the halalness of products which include the provision of materials, processing, storage, packaging, distribution, sale, and presentation of products. HPP companion in this case are in charge of assisting Micro, Small and Medium Enterprises (MSME) actors in fulfilling product halal requirements, in order to carry out halal certification obligations. The position of a halal product process (HPP) companion who is also an extension officer is very important in assisting the halal certification process for MSMEs. Their knowledge, example and experience must be integrated with the needs of MSMEs who will manage halal certification in their products. A companion or extension worker is a person who works as an adviser, idea giver, lightener, guide and director. HPP companion are required to build public confidence about the importance of halal and good food and the dangers of non-halal food for health in order to encourage the development of MSMEs to become one of the sources of regional and national economic growth.